2019
DOI: 10.1242/jcs.233130
|View full text |Cite
|
Sign up to set email alerts
|

A direct interaction between survivin and myosin II is required for cytokinesis

Abstract: An acto-myosin contractile ring, which forms after anaphase onset and is highly regulated in time and space, mediates cytokinesis, the final step of mitosis. The chromosomal passenger complex (CPC), composed of Aurora-B kinase, INCENP, borealin and survivin (also known as BIRC5), regulates various processes during mitosis, including cytokinesis. It is not understood, however, how CPC regulates cytokinesis. We show that survivin binds to non-muscle myosin II (NMII), regulating its filament assembly. Survivin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…This may also be true for the survivin-ran interaction [29,37]. However, this is not always the case, as most recent studies have indicated that during non-muscle myosin II (NMII)-mediated cytokinesis, only the survivin homodimer binds to NMII, attesting to the biological importance of survivin homodimerization [38]. Nevertheless, it would be intriguing to discover whether the currently identified survivin homodimerization inhibitors such as LQZ-7 and LQZ-7F could also disrupt survivin-Borealin or survivinran interactions.…”
Section: Lqz-7 and Lqz-7fmentioning
confidence: 99%
“…This may also be true for the survivin-ran interaction [29,37]. However, this is not always the case, as most recent studies have indicated that during non-muscle myosin II (NMII)-mediated cytokinesis, only the survivin homodimer binds to NMII, attesting to the biological importance of survivin homodimerization [38]. Nevertheless, it would be intriguing to discover whether the currently identified survivin homodimerization inhibitors such as LQZ-7 and LQZ-7F could also disrupt survivin-Borealin or survivinran interactions.…”
Section: Lqz-7 and Lqz-7fmentioning
confidence: 99%
“…At the molecular level, survivin forms the chromosomal passenger complex (CPC) with inner centromere protein (INCENP), borealin (also known as Dasra), and Aurora B kinase and proper formation (and localization) of the CPC during M phase of the cell cycle are both crucial for the completion of mitosis [64,65]. Interestingly, a recent study revealed that the survivin homodimer interacts with myosin II to regulate cytokinesis [66]. Therefore, survivin is widely accepted as a multi-functions protein, which is capable of inhibiting caspase-dependent and -independent apoptosis through both direct and indirect modulations and promoting mitosis through formation of the CPC in cancer cells.…”
Section: Survivin As An Apoptosis Inhibitor and A Mitosis Positive Rementioning
confidence: 99%
“…Thus, RhoA is required for AMR assembly in mammalian cells ( Figure 4B; Basant and Glotzer, 2018;Verma et al, 2019). The chromosomal passenger complex (CPC), including its components Aurora B and survivin, appears to regulate IIB localization during the abscission stage ( Figure 4B; Kondo et al, 2013;Babkoff et al, 2019). Similar to Myo1 in budding yeast (Fang et al, 2010), the central region of the IIA tail (residues 834-1,632) is required for its localization to the division site (Figure 1), but its tethering factor at the division site remains unknown (Beach and Egelhoff, 2009).…”
Section: Localization and Dynamics Of The Nm-iia -Iib And -Iic Durimentioning
confidence: 99%